[latex]6y-(3y+4)=y\\----------------\\-(3y+4)=-1(3y+4)\ \ \ |use\ distributive\ property\ a(b+c)=ab+ac\\-1(3y)-1(4)=-3y-4\\----------------------------\\6y-(3y+4)=y\\6y-3y-4=y\\3y-4=y\ \ \ \ |add\ 4\ to\ both\ sides\\3y-4+4=y+4\\3y=y+4\ \ \ \ \ |subtract\ "y"\ from\ both\ sides\\3y-y=y-y+4\\2y=4\ \ \ \ |divide\ both\ sides\ by\ 2\\2y:2=4:2\\\huge\boxed{y=2}[/latex] [latex]check:\\6y-(3y+4)=6(2)-(3(2)+4)=12-(6+4)=12-10=2\\\\correct\ :)[/latex]

6y - (3y + 4) = y equals y = 2. First, simplify brackets. / Your problem should look like: 6y - 3y - 4 = y. Second, simplify 6y - 3y - 4 to 3y - 4. / Your problem should look like: 3y - 4 = y. Third, subtract 3y from both sides. / Your problem should look like: -4 = y -3y. Fourth, simplify y - 3y to -2y. / Your problem should look like: -4 = -2y. Fifth, divide both sides by -2. / Your problem should look like: [latex] \frac{-4}{-2} [/latex] = y. Sixth, simplify [latex] \frac{-4}{-2} [/latex] to [latex] \frac{4}{2} [/latex]. / Your problem should look like: [latex] \frac{4}{2} [/latex] = y. Seventh, simplify [latex] \frac{4}{2} [/latex] to 2. / Your problem should look like: 2 = y. Eighth, switch sides. / Your problem should look like: y = 2, which is your answer.